Mechanisms Suspended Solids Removal Model of Wastewater from Nursing of Tadpoles (Hoplobatrachus rugulosus) Farm by Physical Filtration System - Iniam, Prinyawat; Intaravicha, Nuttakorn (Journal of Vocational Education in Agriculture, 2024)
The objectives of this study were 1) to study wastewater quality and 2) to create a wastewater treatment model by draining water and settling from tadpole nursery ponds. The study method was divided into two steps: Step 1: Experimental nursery for tadpoles for 30 days to compare the difference in growth rates by t-test statistics at a confidence level of 95 percent between the traditional tadpole nursery, where water changes every day, and the carrying capacity condition nursery, which never changes the water. The wastewater quality was analyzed for constructing the wastewater treatment model in step 2. The results of the study showed that the weight and length of the traditional tadpole nursery were significantly higher than those of the carrying capacity nursery. At a statistical confidence level of 95 percent, the results of the water quality study showed that the turbidity did not pass the standard for effluent discharge from freshwater aquaculture ponds from day 4. Step 2: Apply the Beer-Lambert model to design a wastewater treatment system. The study found that choosing to use the upper sieve No. 60 mesh and the lower sieve No. 400 mesh can decrease the number of suspended solids in the water, which tends to decline the most. The results of both objectives showed that for 30 days of rearing, the wastewater treatment system should transfer water every 3 days by filtering sediment and delaying the time of sedimentation by selecting the upper sieve No. 60 mesh and lower sieve No. 400 mesh before being released into the environment.